Perilaku Plate Girder Badan Bergelombang - Arya Rizki Darmawan; Agoes Soehardjono; Wisnumurti Wisnumurti (Department of Civil Engineering, Faculty of Engineering, University of Brawijaya, 2017)
Plate girder is a composition from of several pieces of plate elements that have high slender ratio. Buckling on web is the main problem. Corrugated web is an innovation to resolve buckling problems. This research aims to get the effect of fold angle to shear capacity and get the collapse behavior that occurred. The research was conducted on a full scale in the laboratory and the ANSYS validation. This research concludes that the shear capacity of a flat-plate girder (conventional) will be increase by about 41% by making corrugated web geometric. In this research, the collapse occured in conventional girder plate is the collapse due to diagonal shear buckling in the area of 1/3 support, while for the collapse of the corrugated web girder is the collapse of torsion.